Forecasting the number of foreign tourists visiting Indonesia during the Covid-19 Pandemic - Sawitri, Retnaning Ayu Dyah; Eltivia, Nurafni; Riwajanti, Nur Indah (Journal of Sustainable Tourism and Entrepreneurship, 2021)
Purpose: This study aims to predict the number of foreign tourists who come to Indonesia during the pandemic. Research Methodology: Forecasting using the Holt-Winters Multiplicative method and secondary data, namely the number of foreign tourists visiting Indonesia obtained from the website of the Central Statistics Agency. Results: Based on the forecast, in November and December 2021, the number of foreign tourists visiting Indonesia will increase because it coincides with the Christmas and New Year holidays. However, from January-October 2022, the visit rate continued to decline. The possibility of an increase in confirmed cases of COVID-19 due to the December forecast, namely the increased mobility of people to tourist destinations to spend the holiday, could be due to the global economic crisis due to COVID-19 cases. Limitations: The number of foreign tourist visits data on the Central Bureau of Statistics website is only available from early 2017 to October 2021. Contribution: Forecasting results can be used as a reference for the Indonesian government in formulating policies in anticipating the arrival of foreign tourists during the pandemic so that the recovery of the economic sector can be maximized.